Hate Speech, Agama, dan Kontestasi Politik di Indonesia - Winda Wana Utami; Darmaiza Darmaiza (Indonesian Journal of Religion and Society, 2020)
The aim of this study is to explain the types of hate speech on Facebook and Instagram related to the political contestation of Joko Widodo as President in 2014, presidential candidate in 2019, and Basuki Tjahaja Purnama, Governor of DKI Jakarta in 2017. This research uses a content analysis approach. The result of study found several types that can be categorized as hatespeech, namely in the form of satire/sarcasm, hoaxs, cursing, distortion, insults, and negative criticism. The orientation that used in political moments is related to religion with regard to religious ideology. The term religion is used as a ripertoir for mobilizing, and the issue of ethnic, religion, race and groups (SARA) is used as a means of emphasizing political opponents. This study concludes that the current trend of political contestation is intertwined with the increasing politics of identity, religion and hatespeech as a form of democracy without morals.